PARENTS' PERCEPTIONS OF THE USE OF GADGETS IN CHILDREN AGED 5-6 YEARS - Fitriyani, Eka Setiawati, Subhan (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This study aims to determine parents' perceptions of the use of gadgets in children aged 5-6 years at PAUD At Taqwa, Tunjung Teja sub-district, and identify factors that influence parents' perceptions of the use of gadgets in children of that age. The population in this study included all students aged 5-6 years at PAUD At Taqwa, with the sampling technique using random sampling. Data were collected through observation and interviews. Data analysis was conducted using the Miles and Huberman method, which includes data reduction, data presentation, and conclusion drawing. The results of the study revealed two main findings: first, parents' perceptions of the use of gadgets in children tend to be negative, due to the assumption that gadgets have more negative impacts than positive; second, there are three factors that influence parents' perceptions, namely the level of parental education, understanding of the negative impacts of using gadgets, and controlling the use of gadgets.